Genetic analysis of resistance to stem rot pathogen (Macrophomina phaseolina) infecting jute - DE, D.K.; Kaiser, S.A.K.M. (Pesquisa Agropecuaria Brasileira, 1991)
To study the inheritance as well as combining abilities for resistance to stem rot disease [Macrophomina phaseolina (Tassi) Goid.] in jute (Corchorus olitorius L.) the diallel crosses among seven varieties excluding the reciprocals were evaluated against this disease under 'sick plot' condition on the Gangetic plains of West Bengal, India during the months from May to September ('kharif' season) of 1989. Genetic analysis of the data showed that additive gene effect was predominant over nonadditive gene effect. General combining ability (gca) effect showed that the parents Russian red, Sudan green, Tanganyka and JRO-878 were the best general combiners towards desirable direction of resistance to this disease, while the specific combining ability (sca) effect was recorded to be highest in the cross Peking x JRO-7835 where both parents had undesirable gca effect. Some of the good general combiners also produced desirable sca effect in some of the cross combinations such as Russian red x JRO-878, Sudan green x JRO-878 and Tanganyka x Russian red. Average disease index of the parents and their F1 progenies further showed that resistance to stem rot pathogen M. phaseolina was dominant over susceptibility.